Decarboxylative Formylation of Aryl Halides with Glyoxylic Acid by Palladium Catalysis under Oxygen - Cao, Hualiang; Pu, Weiwen; Zhang, Jie; Yan, Peijun; Zhang, Jun; Xu, Sheng (Synlett, 2020)
A new free radical/palladium cooperative catalyzed formylation of aryl halides with glyoxylic acid as the formyl source under oxygen conditions has been developed. Various aromatic and heteroaromatic aldehydes were produced in medium to good yields.
Keywords: aryl halide; reductive carbonylation; aldehydes; palladium catalysis; synthetic methods